Pengembangan Video Tutorial Cara Penggunaan Face Tape untuk Rias Geriatri pada Mata Kuliah Tata Rias Wajah - Angelica Sugiono; Titin Supiani; Lilis Jubaedah (Mathematics Education Study Program, 2025)
The result of the research carried out is a video tutorial that will be used as a learning medium in the Makeup Course. The video tutorials used have the aim of helping students to be able to properly understand the material being taught because these video tutorials can be watched and studied repeatedly without being hindered by limited time or space. The method used in the research carried out is the Research and Development method using the ADDIE model, ncludes Analysis, Design, Development, Implementation and Evaluation. This research and development has passed validation test by material and media experts, and practicality test by students. In the results of the validation test carried out by material experts, a score of 82% was obtained, which was in the